Case Report: Anterior Scleritis Presenting as a Primary Ocular Manifestation in Multisystem Inflammatory Syndrome in Children With COVID-19 - Matsubara, Daisuke; Tamura, Daisuke; Kasuya, Yuka; Mizobe, Yoshitaka; Hiwada, Mami; Seki, Mitsuru; Makino, Shinji; Yamagata, Takanori (Frontiers in Pediatrics, 2022)
Multisystem inflammatory syndrome in children (MIS-C) is a newly defined hyperinflammatory disease linked to antecedent coronavirus disease 2019. Patients with MIS-C present with various symptoms, and ocular findings such as mild bilateral conjunctivitis are relatively common. However, detailed descriptions of severe ocular reports associated with MIS-C are scarce in the current literature. Here we report a case of MIS-C in a Japanese boy, with severe eye manifestations in the form of anterior scleritis as the primary MIS-C symptom. Detailed ocular examinations by ophthalmologists may be key for clarifying the pathophysiology of MIS-C.